The Effect of the Treffinger Learning Model on the Learning Outcomes of Grade X Students in the Fiqh Subject at MAN 3 Ngawi - Nurhafizah; Dede asrori Rohim (al-Afkar, Journal For Islamic Studies, 2026)
Fiqh subject in Madrasah Aliyah is an important component in forming an understanding of Islamic laws that can be applied in everyday life. Based on the results of interviews with Fiqh teachers at MAN 3 Ngawi, it is known that the achievement of maximum learning outcomes has not been proven by a decrease in student grades caused by conventional learning models that do not motivate student to think critically and creatively. To overcome this problem, this study applies the Treffinger learning model, which is known to be effective in developing students’ creative thinking and problem solving skills. This study aims to analyze the effect of Treffinger learning model on learning outcomes of grade X students in Fiqh subjects at MAN 3 Ngawi. This study used a quantitative method with a True Experimental design, which involved a pretest-posttest control group design. The Experimental class was tauhgt with the Treffinger model, while the control class used a conventional learning model. The results of the analysis using the T-test with the help of IBM SPSS 25 showed that there was a significant difference between the learning outcomes of the experimental and control classes, where the experimental class showed a better improvement in learning outcomes. Research using the Independent Simple T-Test test with a Sig (2-tailed) value of 0,005. So that 0,005 < 0,05, it can be seen that Ha is accepted and Ho is rejected. Which means that there is an effect of Treffinger learning model on the learning outcomes of class X students in fiqh subject at MAN 2 Ngawi. This, the Treffinger learning model is proven to be effective in improving students’ Fiqh learning outcomes.